Morfologia błony zaćmy wtórnej u dziecka po operacji zaćmy wrodzonej – opis przypadku - Kanigowska, Krystyna; Grajkowska, Wiesława; Grałek, Mirosława; Pronicki, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
In younger children it is advantageous to perform cataract surgery with posterior capsulectomy and anterior vitrectomy to prevent secondary cataract formation. In many cases after surgery lens epithelial cells grow on the posterior lens capsule, and on the anterior surface of the vitreous. Authors report a case of secondary cataract in 6 years old girl post pars plana lensectomy and anterior vitrectomy in both eyes. They performed secondary posterior chamber IOL implantation and examined the fibrous tissue resection (secondary cataract), from the left eye – histological and immunohistochemical tests. This examination with H&E staining revealed the presence of fibroblast-like cells. The lens epithelial cells probably underwent epithelial-mesenchymal transformation and in some cases can create secondary cataract.